2021
DOI: 10.26434/chemrxiv.13661081
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Outstanding Nobility Observed in Cu5 Clusters Reveals the Key Role of Collective Quantum Effects

Abstract: Subnanometer-sized metal clusters often feature a molecule-like electronic structure, which makes their physical and chemical properties significantly different from those of nanoparticles and bulk material. Considering potential applications, there is a major concern about their thermal stability and susceptibility towards oxidation. Cu clusters of only 5 atoms (Cu<sub>5</sub> clusters) are first synthesized in high concentration using a new-generation wet chemical method. Next, it is shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(22 citation statements)
references
References 28 publications
4
18
0
Order By: Relevance
“…Our selection is based on previous experimental measurements on the catalytic activity of Au n clusters (with n in between 3 and 10) for the oxidation of thiophenol, showing that the Au 5 cluster holds the best performance. 49 30 when the cluster size is reduced to a very small number of atoms, a sub-nanometer network of discrete molecule-like d orbitals centered on the metal atoms is formed. The special structures of these molecular orbitals favor that the metal atoms become cooperatively active in the given (e.g., substitution) process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our selection is based on previous experimental measurements on the catalytic activity of Au n clusters (with n in between 3 and 10) for the oxidation of thiophenol, showing that the Au 5 cluster holds the best performance. 49 30 when the cluster size is reduced to a very small number of atoms, a sub-nanometer network of discrete molecule-like d orbitals centered on the metal atoms is formed. The special structures of these molecular orbitals favor that the metal atoms become cooperatively active in the given (e.g., substitution) process.…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, our findings reveal the major structural fluxionality of triade clusters compared with extended surfaces. As shown on a study of the oxidation quenching of Cu 5 clusters, when the cluster size is reduced to a very small number of atoms, a sub-nanometer network of discrete molecule-like d orbitals centered on the metal atoms is formed. The special structures of these molecular orbitals favor that the metal atoms become cooperatively active in the given (e.g., substitution) process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One major concern has been on the stability of Cu 5 clusters in an O 2 -rich atmosphere as it is generally assumed that nanoparticles suffer from an increasing susceptibility to oxidation with decreasing size. Opposing that assumption, recent works have indicated that Cu 5 clusters experience reversible oxidation, 7,[9][10][11][12][13] making them paradigmatic.…”
Section: Introductionmentioning
confidence: 99%
“…The most recent experimental evidences have shown the reversible oxidation of surface-supported Cu 5 clusters at thermodynamical equilibrium by in situ X-ray Absorption Spectroscopy and X-ray Photoelectron Spectroscopy. 13 Highly Oriented Pyrolitic Graphite (HOPG) was considered as a chemically inert support, different oxygen gas pressures, and a temperature range going from roomtemperature (RT) up to 773 K. 13 In general, the interaction of molecular oxygen with metal and metal oxides such as TiO 2 rutile (110) has been a longstanding problem over the last decades as extensively reviewed by Yates's [15][16][17] and Henderson's 18,19 groups from an experimental perspective. As shown in the earliest first-principles studies, [20][21][22][23][24] molecular oxygen can be adsorbed onto TiO 2 rutile (110) as either a superoxo O − 2 radical or a peroxo O 2− 2 species, both in molecular and dissociative forms, existing several (photo-)desorption channels as well.…”
Section: Introductionmentioning
confidence: 99%